Bile acid metabolism dysregulation associates with cancer cachexia: roles of liver and gut microbiome. Issue 6 (28th September 2021) - Feng, Lixing; Zhang, Wanli; Shen, Qiang; Miao, Chunxiao; Chen, Lijuan; Li, Yiwei; Gu, Xiaofan; Fan, Meng; Ma, Yushui; Wang, Hui; Liu, Xuan; Zhang, Xiongwen
Abstract: Background: Cancer cachexia is a multifactorial metabolic syndrome in which bile acid (BA) metabolism might be involved. The aim of the present study was to clarify the contribution of liver and gut microbiota to BA metabolism disturbance in cancer cachexia and to check the possibility of targeting BA metabolism using agents such as tauroursodeoxycholic acid (TUDCA) for cancer cachexia therapy. Methods: The BA profiles in liver, intestine, and serum of mice with cancer cachexia induced by inoculation of colon C26 tumour cells were analysed using metabolomics methods and compared with that of control mice. Proteomic analysis of liver protein expression profile and 16S rRNA gene sequencing analysis of gut microbiota composition in cancer cachexia mice were conducted. Expression levels of genes related to farnesoid X receptor (FXR) signalling pathway in the intestine and liver tissues were analysed using RT–PCR analysis. The BA profiles in serum of clinical colon cancer patients with or without cachexia were also analysed and compared with that of healthy volunteers. The effects of TUDCA in treating cancer cachexia mice were observed. Results: In the liver of cancer cachexia mice, expression of BA synthesis enzymes was inhibited while the amount of total BAs increased ( P < 0.05). The ratios of conjugated BAs/un‐conjugated BAs significantly increased in cancer cachexia mice liver ( P < 0.01). Gut microbiota dysbiosis such as decrease in Lachnospiraceae and increase in Enterobacteriaceae was observed in the intestine of cancer cachexia mice, and microbial metabolism of BAs was reduced. Increase in expression of FGF15 in intestine ( P < 0.01) suggested the activation of FXR signalling pathway which might contribute to the regulation of BA synthesis enzymes, transporters, and metabolic enzymes. Increase in the BA conjugation was observed in the serum of cancer cachexia mice. Results of clinical patients showed changes in BA metabolism, especially the increase in BA conjugation, and also suggested compensatory mechanism in BA metabolism regulation. Oral administration of 50 mg/kg TUDCA could significantly ameliorate the decrease in body weight ( P < 0.001), muscle loss ( P < 0.001), and atrophy of heart and liver ( P < 0.05) in cancer cachexia mice without influence on tumour growth. Conclusions: Bile acid metabolism dysregulation such as decrease in BA synthesis, increase in BA conjugation, and decrease in BA microbial metabolism was involved in development of cancer cachexia in mice. Targeting BA metabolism using agents such as TUDCA might be helpful for cancer cachexia therapy.